Behind the Bylines: News Writing Skills of Cagayan State University Lal-lo Campus Journalists - Benmar B. Torres (Journal of Research in Education and Pedagogy, 2026)
This embedded mixed-method research examined Cagayan State University (CSU) Lal-lo campus journalists’ proficiency in News Writing by integrating quantitative and qualitative approaches. The quantitative component involved assessing students’ news articles through an expert-validated rubric based on a five-point scale, focusing on headline construction, lead writing, overall organization, and use of references, all aligned with Associated Press (AP) standards. Analysis of inter-rater reliability indicated acceptable to strong agreement among the three evaluators, as reflected in both Cronbach’s Alpha and the Intraclass Correlation Coefficient. For the qualitative aspect, evaluators’ written comments within the rubric were analyzed to gain in-depth insights into the students’ writing skills and challenges. The data were treated using descriptive statistical methods alongside thematic analysis. Results showed that student journalists generally displayed adequate skills in news writing, particularly in demonstrating clarity, accuracy, ethical considerations, and basic formatting in headlines and attribution following standard guidelines. However, they encountered challenges in crafting concise and effective leads and in sustaining consistent structure throughout their articles. The findings further indicated that students had difficulty identifying appropriate news angles, organizing ideas logically, and applying the conventional inverted pyramid structure. Lead writing emerged as a key area needing improvement, reflecting limitations in recognizing essential facts and determining news value. Additionally, their outputs revealed issues related to completeness, verbosity, grammatical accuracy, angle selection, and identifying suitable lead types. In response to these concerns, the study recommends implementing targeted instructional strategies, such as regular lead-writing exercises, headline revision workshops, peer evaluation activities, and focused grammar instruction to strengthen students’ overall news writing abilities.